Soil salinity management practices in coastal area of Bangladesh: a review - Shawkhatuzamman, Mohammed; Roy, Sumona Rani; Alam, Md Zahanggir; Majumder, Premangshu; Anka, Nushrat Jahan; Hasan, Ahmed Khairul (Research in Agriculture Livestock and Fisheries, 2023)
Soil salinity is a significant threat to agriculture and livelihood, particularly in the Southern coastal areas of Bangladesh. Soil salinity is extended from 0.833 to 1.056 million hectares (about), with an increase of 26% between 1973 and 2009. Out of about 1.689 million hectares of coastal land, about 1.056 million hectares are affected by soil salinity of various degrees covering 49 Upazila (sub-district) of 19 districts. About 0.328, 0.274, 0.189, 0.161, and 0.101 million hectares of land are affected by very slight (S1), slight (S2), moderate (S3), strong (S4), and very strong salinity (S5), respectively. Data recorded by SRDI manifests new ingression of salinity in Narail (18.71 ha), Jashore (14.99 ha), Barishal (13.96 ha), Gopalgonj (6.27 ha), Jhalakati (4.69 ha), and Madaripur (0.72 ha) districts. Soil salinity also encroached a large area of Bhola (53.84 ha), Patuakhali (40.08 ha), Khulna (27.92 ha), and Bagerhat (23.14 ha), besides minor ingression in other districts. The salinity level is almost double (2.8-18.5 to 4.0-42.8 dS/m) from 1973 to 2009 in Sharankhola Upazila of Bagerhat district, Dumuria Upazila of Khulna district and Shyamnagar Upazila of Satkhira district (SRDI, 2010). Different causes are involved in increasing the water and soil salinity of the coastal area of Bangladesh, like withdrawal of fresh river water from upstream, irregular rainfall, faulty management of sluice gates and polders, regular tidal water flooding in an unprotected area, the capillary rise of soluble salts, decreased surface water availability, lowered ground water table, reduced soil moisture content, the introduction of unplanned shrimp cultivation, lack of drainage facilities. Some of the widespread soil and land management techniques adopted in the saline areas of Bangladesh to cope with the salinity are polder (123), farm-pond (khamar-pokor), sarjan procedure, usage of raised shrimp farm bund for year-round cropping, mulching (keeping land covered in winter and summer months), land leveling, pitcher (kolosh) irrigation to grow watermelon, dibbling method, the addition of organic matter, chemical fertilizers and cultivation of saline tolerant crop varieties, particularly rice. Vol. 10, No. 1, April 2023: 1-7